Program Peningkatkan Mutu Madrasah Diniyah Al-Ichsan Petungombo Kediri Melalui Pembinaan Tata Kelola Administrasi - Aji Wahyudin; Muhammad Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Madrasah diniyah al-ichsan is an Islamic educational institution which on January 6, 2020, which is among the first madrassas in the village of Depawon plosoklaten district kediri. In this condition requires to always try to make improvements in every line including shaping the quality of education. The head of the madrassa has a very important role to control and move all madrassa citizens in order to realize common ideals. One of the common ideals in educational institutions is the quality of education, while the quality of education is something that must be fought for and maintained. For this reason, this study aims to find out efforts to improve the quality of education in madrasah diniyah related to the governance of education administration. This study is a qualitative descriptive study and was conducted at madrasah diniyah al-ichsan petungombo, on August 4 to August 25, 2020. The subjects in the study were the head of the madrassa diniyah al-ichsan as the administrator of the madrassa, while the informant was the deputy head of the madrassa, the secretary and treasurer of the madrassa, the teacher, the student and the guardian of the student. Data collection techniques in this study are carried out by observation, interview and documentation. In data validity testers used source triangulation techniques and methods. While data analysis uses interactive qualitative analysis with program implementation steps using POAC and data collection methods, data reduction, data presentation, and conclusion withdrawal. Based on the results of the implementation showed that in improving the quality of education in madrasah diniyah al-ichsan petungombo seen in its administrative governance. As for efforts in improving the quality of education related to administration there are several indicators that need to be achieved, namely: input indicators are to regulate good administrative governance, prepare professional educators; good through construction; discussions or meetings; conduct training, as well as increase the development of student interest talent. Efforts in improving the quality of education in relation to process indicators are conditioning a safe learning environment; comfortable; and stimulate in learning, making programs in accordance with the needs of students including; memorize short letters, memorize do'a-do'a; mentoring the recitation of the Qur'an; worship; extracurricular activities, providing learning motivation; Both reward teachers and students. Efforts in improving the quality of education in relation to output indicators, are trying to excel in academic and non-academic.